Assessment of the environmental quality of two urbanized lotic systems using multiple indicators - Calderon, Mirian Roxana (2017)
Urbanization impacts ecosystems, generating habitat loss and fragmentation, loss of diversity, increase in runoff and contaminant discharges, and the establishment of exotic species. Potrero de los Funes Village (San Luis-Argentina), not only suffers from the increase of its population during summer months due to tourism, but also from an accelerated growth of its permanent population. In order to evaluate the potential effects of urbanization, the environmental quality of Potrero de los Funes River and Las Chacras Stream was assessed, using physical-chemical and biological indicators. Macroinvertebrates, through the application o the Biotic Index for San Luis Sierras (BISLS), anuran amphibian richness and relative abundance, and riparian vegetation were used as bioindicators, whereas a Simplified Index of Water Quality (SIWQ) was used to characterize the physical-chemical quality of water at each site. SIWQ and BISLS scores were significantly different between sites (F7,28 = 9.88, p < 0.001 and F7,28 = 24.18, p < 0.001 respectively). SIWQ was significantly correlated with BISLS (Spearman correlation coefficient = 0.8, p < 0.001). Four anuran species were registered along Potrero River, with no significant differences in the intensity of vocalizations between sites. No species were detected in Las Chacras Stream. Average total plant species richness, exotic plants richness and vegetation cover were higher at the most impaired system, Las Chacras Stream. The Principal Component Analysis showed that the first two PCs explained 76.3% of the total variance. PC1, with strong loadings of SIWQ, BISLS, and amphibian richness, was principally driven by chemical water quality and biological conditions. PC2 was mainly determined by plant richness. The chemical and biological water quality of Potrero and Las Chacras is somewhat impaired being the upper Las Chacras Stream the most compromised area. This study provides information that will certainly be used to manage future impacts of urbanization on aquatic resources.